Relationship Between Psychosocial Distress in Pregnancy and Two Genes Associated With Human Social Interaction: A Pilot Study - Sarah Dewell MSc, RN; Donna Slater PhD; Karen Benzies PhD,RN; Sheila McDonald PhD; Suzanne Tough PhD (SAGE Publishing, 2018)
Background Prenatal depression, anxiety, and stress (prenatal psychosocial distress) are common, and several environmental risk factors have been implicated in their development. Variation in genes, specifically single nucleotide polymorphisms (SNPs), may explain why some women develop maternal mental health concerns while others do not. Purpose The purpose of this pilot study was to determine the feasibility of completing SNP analyses using whole blood collected prenatally between 2008 and 2011. We examined the association between SNPs in two genes ( FKBP5 and OXTR ) among women with low and high prenatal psychosocial distress. Methods A subset ( N  = 50, 25 high and 25 low prenatal psychosocial distress) of participants was selected from the All Our Families pregnancy cohort. DNA was extracted from maternal blood and used for selected SNP analysis. Participants' scores on the Edinburgh Prenatal Depression Scale, Spielberger State Anxiety Inventory, and Perceived Stress Scale were used along with demographic variables. Results Genotype distribution was not significantly different between the low and high prenatal psychosocial distress groups for either the FKBP5 or the OXTR SNP ( p  = .699 and p  = .125). After controlling for maternal age and income, women with the GG genotype at the OXTR SNP (rs237885) were statistically less likely to be in the high prenatal psychosocial distress group ( p  = .037). Conclusion OXTR SNP rs237885, maternal age, and lower income were associated with prenatal psychosocial distress. This pilot study demonstrated the feasibility of continuing to a larger study that incorporates additional environmental and genetic information.